Answer:
Answer: Option d. (-63) is the sum of first 6 terms
Explanation:
Given sequence is 3-6+12-24+...........
We know the formula for the sum of the sequence be
S(6) = A(1)×
![(1-r^(n) )/(1-r)](https://img.qammunity.org/2020/formulas/mathematics/high-school/d8hve58bm2lct55of3vuzjzrqeb9ymntj8.png)
From the given question n= 6
A(1) = 3
and common ratio r = (-6)/3 = (-2)
Now we put these values in the formula
S(6) = 3×
![(1-(-2)^(6) )/(1-(-2))](https://img.qammunity.org/2020/formulas/mathematics/high-school/t6jn1kcm54ohrowsbaurdis07gi5sc0tq6.png)
= 3×
![((1-(-2)^(6) )/(3)](https://img.qammunity.org/2020/formulas/mathematics/high-school/nxonyihbd58wwyd8ikfj033ego5hj3xmu7.png)
= 3×(1-64)/3
= 3×(-63)/3
= (-63)
So the sum of six terms is (-63).